Legislative bargaining with joint production: an experimental study - Merkel, Anna; Vanberg, Christoph (Discussion paper series, 2019)
We conduct 3-person bargaining experiments in which the surplus being divided is produced by completing a prior task. Using a Baron-Ferejohn framework, we investigate how differences in contributions to production affect bargaining under different decision rules. Under unanimity rule, all proposals and agreements constitute convex combinations of the equal and proportional splits. Contrary to our predictions, this pattern largely persists under majority rule. In sharp contrast to prior experiments in which an exogenous surplus is divided, few subjects attempt to build minimum winning coalitions when the surplus is jointly produced.
Keywords: Graue Literatur